Baseline mean and heterogeneity of MR cartilage T2 are associated with morphologic degeneration of cartilage, meniscus, and bone marrow over 3years – data from the Osteoarthritis Initiative - Joseph, G.B.; Baum, T.; Alizai, H.; Carballido-Gamio, J.; Nardo, L.; Virayavanich, W.; Lynch, J.A.; Nevitt, M.C.; McCulloch, C.E.; Majumdar, S.; Link, T.M. (Osteoarthritis and cartilage, 2012)
The purpose of this study is to determine whether the mean and heterogeneity of magnetic resonance (MR) knee cartilage T2 relaxation time measurements at baseline are associated with morphologic degeneration of cartilage, meniscus, and bone marrow tissues over 3years in subjects with risk factors for osteoarthritis (OA). Subjects with risk factors for OA (n=289) with an age range of 45–55years were selected from the Osteoarthritis Initiative (OAI) database. 3.0 Tesla MR images were analyzed using morphological gradings of cartilage, bone marrow and menisci whole-organ magnetic resonance imaging scores (WORMS scoring). A T2 mapping sequence was used to assess the mean and heterogeneity of cartilage T2 (gray level co-occurrence matrix texture analysis). Regression models were used to assess the relationship between baseline T2 parameters and changes in morphologic knee WORMS scores over 3years. The prevalence of knee abnormalities in the cartilage (P<0.0005), meniscus (P<0.00001), and bone marrow significantly (P<0.00001) increased from baseline to 3years in all compartments combined. The baseline mean and heterogeneity of cartilage T2 were significantly (P<0.05) associated with morphologic joint degeneration in the cartilage, meniscus and bone marrow over 3years. The prevalence of knee abnormalities significantly increased over 3years; increased cartilage T2 at baseline predicted longitudinal morphologic degeneration in the cartilage, meniscus, and bone marrow over 3years in subjects with risk factors for OA.